2007
DOI: 10.1111/j.1440-1746.2006.04707.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of antiviral therapy with lamivudine after initial treatment for hepatitis B virus‐related hepatocellular carcinoma

Abstract: It is suggested that lamivudine therapy is beneficial for patients after initial treatment for HBV-related HCC because it contributes to improving remnant liver function, thus decreasing the risk of liver failure and increasing the chances of receiving available treatment modalities for recurrent HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
144
3

Year Published

2010
2010
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(152 citation statements)
references
References 25 publications
5
144
3
Order By: Relevance
“…The cumulative HCC recurrence rate of the patients treated with IFN-alfa and the control group was 25 and 40% at the end of 1 year and 47 and 90% at the end of 4 years, respectively (P = 0.0135). Furthermore, this study also showed that the prevention of HCC recurrence using IFN-alfa was effective in HBV-related HCC [392] Lamivudine A retrospective study was conducted to evaluate the efficacy with or without using LAM in patients following curative ablation of HBV-related HCC [393]. Cumulative recurrence rates of HCC were not significantly different between two groups (P = 0.622).…”
Section: Tertiary Prevention For Hbv-related Hccmentioning
confidence: 98%
See 1 more Smart Citation
“…The cumulative HCC recurrence rate of the patients treated with IFN-alfa and the control group was 25 and 40% at the end of 1 year and 47 and 90% at the end of 4 years, respectively (P = 0.0135). Furthermore, this study also showed that the prevention of HCC recurrence using IFN-alfa was effective in HBV-related HCC [392] Lamivudine A retrospective study was conducted to evaluate the efficacy with or without using LAM in patients following curative ablation of HBV-related HCC [393]. Cumulative recurrence rates of HCC were not significantly different between two groups (P = 0.622).…”
Section: Tertiary Prevention For Hbv-related Hccmentioning
confidence: 98%
“…However, median C-P score at the time of HCC recurrence was significantly different in the control group (P = 0.005). The cumulative survival rates of patients in the LAM group tended to be higher than those of patients in the control group (P = 0.063) [393]. The outcome of LAM treatment of patients with controlled HCC in terms C-P score and survival compared with a matched, LAM-untreated cohort showed no significant difference in the cumulative incidence of HCC recurrence and survival between the two groups [394].…”
Section: Tertiary Prevention For Hbv-related Hccmentioning
confidence: 99%
“…Several retrospective studies [21][22][23][26][27][28][29]33,35] showed that NA treatment did not lead to significantly higher recurrence-free survival than non-NA treatment, while other retrospective studies [24,25,[30][31][32]34,36,37] and the RCTs [38,39] showed that NA therapy was associated with significantly higher recurrence-free survival than non-NA treatment.…”
Section: Recurrence-free Survivalmentioning
confidence: 99%
“…These references comprise 17 retrospective studies [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] and 2 RCTs [38,39] . Most of studies come from Asia, including Chinese mainland, Japan, Hong Kong and Tai Wan, which reflects HBV epidemiology and the high incidence of HBV-related HCC in this region.…”
Section: Recurrence-free Survivalmentioning
confidence: 99%
“…In recent years, several reports from Japan have shown improved survival with lamivudine (LAM) therapy in patients following local treatment of HCC. [5][6][7][8] We report the effect of antiviral therapy on long-term survival (some patients approaching >10 years) of CHB patients whose initial HCC is locally ablated. This study was approved by the Institutional Review Board of Thomas Jefferson University.…”
Section: Dear Editormentioning
confidence: 99%